2018
DOI: 10.1016/j.ribaf.2017.07.076
|View full text |Cite
|
Sign up to set email alerts
|

The pass-through to consumer prices in CIS economies: The role of exchange rates, commodities and other common factors

Abstract: This empirical study considers the pass-through of key nominal exchange rates and commodity prices to consumer prices in the Commonwealth of Independent States (CIS), taking into account the effect of idiosyncratic and common factors influencing prices. In order to do that, given the relatively short window of available quarterly observations (1999-2014), we choose heterogeneous panel frameworks and control for cross-sectional dependence. The exchange rate passthrough is found to be relatively high and rapid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
1
18
3
Order By: Relevance
“…We find that the average speed of the pass-through in the CCA is about 10 percent on impact and about 25 percent after 12 months. The average pass-through in the CCA countries is somewhat higher than the pass-through in the CIS countries (Comunale and Simola, 2018) and 28 emerging economies (Caselli and Roitman, 2016), but it is lower compared to the pass-through in Sub-Saharan Africa countries . The pass-through is somewhat higher in CCA energy-importing countries compared to CCA energy-exporting countries, which could be explained by structural differences across these countries (economic diversification, reliance on remittances, proportion of imported goods in CPI baskets).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…We find that the average speed of the pass-through in the CCA is about 10 percent on impact and about 25 percent after 12 months. The average pass-through in the CCA countries is somewhat higher than the pass-through in the CIS countries (Comunale and Simola, 2018) and 28 emerging economies (Caselli and Roitman, 2016), but it is lower compared to the pass-through in Sub-Saharan Africa countries . The pass-through is somewhat higher in CCA energy-importing countries compared to CCA energy-exporting countries, which could be explained by structural differences across these countries (economic diversification, reliance on remittances, proportion of imported goods in CPI baskets).…”
Section: Introductionmentioning
confidence: 72%
“…While Bussiere (2013) for G7 countries and Colavecchio and Rubene (2020) for 19 euro area countries find that the pass-through is higher for exchange rate appreciations, Delatte and Villavicencio (2012) for 4 major developed countries and Caselli and Roitman (2016) for 28 emerging markets find that the pass-through is lower for exchange rate appreciations. Comunale and Simola (2018) for 7 CIS countries find no evidence of sign asymmetries in the pass-through, while Ben Cheikh (2012) for 12 euro area countries finds that the pass-through is higher for exchange rate depreciations in some countries and lower in others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the completion of ERPT is determined by the assumptions of perfectly competitive markets, fully flexible prices and the consistency of law of one price. Thus, it can be inferred that deviations from those situations can cause incomplete ERPT [21]. The vast body of empirical literature on ERPT indicates that pass-through is highest for import prices and lowest for consumer prices, while cross-country variation in the pass-through can be accepted as a major factor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beckmann and Fidrmuc [23] also exposed that the long-run pass-through was around 60% for both currencies. Most recently, [21] studied the ERPT for the case of CIS countries using heterogeneous panel frameworks and control for cross-sectional dependence. It was found that the ERPT was relatively high and rapid for CIS countries in the case of the nominal effective exchange rate, but not significant for the bilateral rate with the US dollar.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Faryna & Simola (2018) also report a high sensitivity to US, euro area, Russian, and Chinese output shocks. In addition, several studies provide evidence for the importance of the CIS region in inflation and exchange rate developments, see Comunale & Simola (2018), Faryna (2016a), Beckmann & Fidrmuc (2013), and Dreger & Fidrmuc (2011).…”
Section: Introductionmentioning
confidence: 99%